The Perception of the Muslim Community of Offie Village, Fakfak Regency Regarding the Hajj Pilgrimage: Persepsi Masyarakat Muslim Kampung Offie Kabupaten Fakfak Terhadap Ibadah Haji - Lekha Sonia; Musthofa Hilmi (Alhadharah: Jurnal Ilmu Dakwah, 2025)
This study examines the perceptions of the Muslim community in Kampung Offie toward the Hajj pilgrimage. It aims to analyze community perceptions based on four aspects: belief, understanding, knowledge, and practice. The research employed a qualitative approach using interviews, observations, and documentation as primary data sources. Data were analyzed through source triangulation. The findings reveal several key points. First, the community’s belief in their ability to perform the Hajj remains relatively low because economic limitations and daily living needs make the pilgrimage a lower priority. However, their spiritual belief remains strong, as they still regard the Hajj as the highest form of worship and a blessing from Allah. Second, the community demonstrates a good understanding of the Hajj, recognizing it as the fifth pillar of Islam and an obligation for Muslims who are financially and physically able. They also view it as a form of spiritual transformation that carries social responsibility. Third, community knowledge about the Hajj varies. Those who have not performed the pilgrimage possess limited knowledge, while those who have performed it demonstrate more comprehensive understanding. Fourth, individuals who have completed the Hajj tend to practice positive social values, while those who have not yet performed it show respect and consider them role models. Overall, religiosity helps maintain positive perceptions despite material limitations. KEYWORDS: public perception ; hajj pilgrimage ; Muslim community ; Offie Village; religiosity.